Prawo przedsiębiorców — nowa jakość i stare problemy - Etel, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The Act of 6th March 2018 — Law of Entrepreneurs came in force on 30th April 2018. It continues the tradition of regulating the principles of undertaking, conducting, and terminating eco-nomic activity with the act on constitutional legitimacy, superior character, tasks and content. This article shows the essence of the reform as well as the construction and scope of the new regulations. Furthermore, it evaluates changes and directs the demands to the legislator
Keywords: law of entrepreneurs; entrepreneurial activity; reform; new legal basis; traditional problems